Shaping Arctic’s Tomorrow through Indigenous Knowledge Engagement and Knowledge Co-Production - Tatiana Degai; Andrey Petrov; Renuka Badhe; Parnuna Egede Dahl; Nina Döring; Stephan Dudeck; Thora Herrmann; Andrei Golovnev; Liza Mack; Elle Omma; Gunn-Britt Retter; Gertrude Saxinger; et al. (Sustainability, 2022)
This perspective presents a statement of the 10th International Congress of Arctic Social Sciences Indigenous Knowledge and knowledge co-production panel and discussion group, 20 July 2021. The statement is designed to serve as a characterization of the state-of-the-art and guidance for further advancement of Indigenous Knowledge and knowledge co-production in the Arctic. It identifies existing challenges and provides specific recommendations for researchers, Indigenous communities, and funding agencies on meaningful recognition and engagement of Indigenous Knowledge systems.